Дослідження та програмна реалізація системи Legrand Cabling System 3 для ЦОД - Фролов, Богдан Вадимович; Frolov, Bogdan (ЦНТУ, 2021)
В даній випускній кваліфікаційній роботі за другим (магістерським) рівнем вищої освіти розроблено програмне забезпечення, яке призначено для системи Legrand Cabling System 3 для ЦОД. Метою розробки є дослідження та програмна реалізація системи Legrand Cabling System 3 для ЦОД. Об’єктом дослідження є процес Legrand Cabling System 3 для ЦОД. Предметом дослідження є методи Legrand Cabling System 3 для ЦОД. Методи дослідження базуються на методах теорії побудови комп’ютерних систем та мереж, методах математичної статистики, методах розробки програмного забезпечення. Результат роботи – програмна реалізація системи Legrand Cabling System 3 для ЦОД. В процесі роботи над програмною моделлю виконано аналіз існуючих апаратних та програмних засобів. В повній мірі описані всі компоненти розробленого програмного забезпечення. Розроблено зручний інтерфейс користувача. Наведені інструкції по роботі з програмними засобами. Програма може використовуватися на ПЕОМ архітектури IBM PC з ОС Windows ХР/Vista/7/8/10. Програму розроблено в середовищі Delphi 10.3.2. In this final qualification work for the second (master's) level of higher education, software has been developed for the Legrand Cabling System 3 for data centers. The purpose of development is research and software implementation of Legrand Cabling System 3 for data centers. The object of research is the process of Legrand Cabling System 3 for data centers. The subject of the study is the methods of Legrand Cabling System 3 for data centers. The research methods are based on the methods of the theory of construction of computer systems and networks, methods of mathematical statistics, methods of software development. The result is a software implementation of the Legrand Cabling System 3 for data centers. In the process of working on the software model, an analysis of existing hardware and software was performed. All components of the developed software are fully described. Developed user-friendly interface. Instructions for working with software are given. The program can be used on a PC architecture IBM PC with Windows XP / Vista / 7/8/10. The program is developed in the Delphi 10.3.2 environment.
Research and software implementation of Legrand Cabling System 3 for data centers
Keywords: комп’ютерна інженерія; Legrand Cabling System 3; ЦОД; computer engineering; data center